2013
DOI: 10.1093/jnci/djt241
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Amino Acid Transport in Metastatic Castration-Resistant Prostate Cancer: Effects on Cell Cycle, Cell Growth, and Tumor Development

Abstract: Inhibition of LAT transporters may provide a novel therapeutic target in metastatic castration-resistant prostate cancer, via suppression of mammalian target of rapamycin complex 1 activity and M-phase cell cycle genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
169
2
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 50 publications
11
169
2
1
Order By: Relevance
“…The knockdown of human LAT1 by small interfering RNAs or stable transduction with lentivirus can also lead to the inhibition of cancer cell growth and migration (27). Similarly, down-regulating LAT1 can lead to decreased growth of prostate cancer cells (28) and human oral cancer cells (29). However, the over-expression of LAT1 has been suggested as a target for combination therapy with anti-proliferative aminopeptidase inhibitors to combat ovarian cancer (30).…”
Section: Clinical Significance Of Lat1 In Tumorsmentioning
confidence: 99%
“…The knockdown of human LAT1 by small interfering RNAs or stable transduction with lentivirus can also lead to the inhibition of cancer cell growth and migration (27). Similarly, down-regulating LAT1 can lead to decreased growth of prostate cancer cells (28) and human oral cancer cells (29). However, the over-expression of LAT1 has been suggested as a target for combination therapy with anti-proliferative aminopeptidase inhibitors to combat ovarian cancer (30).…”
Section: Clinical Significance Of Lat1 In Tumorsmentioning
confidence: 99%
“…It has been reported previously that the overexpression of SLC7 could contribute to the cellular growth and extension of cell cycles and thus, increase susceptibility to cancer (Wang et al, 2013). Thus far, only one study has reported the relationship between SLC7A7 polymorphisms and the development of glioma (Fan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Imaging alternative metabolic pathways, including essential amino acid upregulation, has demonstrated clinical utility for several amino acid analogs [1,2]. survival [3][4][5]. Essential branched chain amino acids have shown a direct influence on critical growth and survival pathways through several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the essential amino acid L-leucine can directly stimulate the growth and survival of a tumor through activation of the critical mTORC1 pathway [3,5]. Inhibiting essential amino acid uptake through targeting amino acid transporters, thereby inhibiting leucine uptake, may offer a new therapeutic opportunity for the treatment of cancers by diminishing tumor growth and metastasis through inhibition of M-phase cell cycle and mTORC1 signaling pathways [4]. Several studies have shown that aggressive, therapy resistant cancers with worse prognosis are associated with overexpression of amino acid transporters such as LAT1 [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%